Career Concerns, Contracts, and Effort Distortions - Andersson, Fredrik (Journal of Labor Economics, 2002)
A two‐period, career‐concerns model with symmetric information but uncertainty about each worker’s ability is analyzed. Contracts are unobservable, but incomes are observable. It is shown that effort is distorted upward by contracts being unobservable and that the distortion depends positively on turnover.